Study of the phylogeny of genera belonging to the subfam. Euphorbioideae (Euphorbiaceae) in the flora of Vietnam - Thanh Nga, Nguyen Thi; Thin, Nguyen Nghia (Academia Journal of Biology, 2006)
In this paper, results in use of NTSYS 2.02 to study the phylogeny of genera belonging to the subfam. Euphorbioideae of Euphorbiaceae in the flora of Vietnam were reported. The dendrogram was presented. It was nearly suitable to the Nguyen Nghia Thin’s classification system of Euphorbiaceae in Vietnam (1999) with difference of the position of the genus Sapium. The dendrogram showed as follows: Sebastiania was related to Excoecaria and both of them belonged to the tribe Hippomaneae; Euphorbia was related to Pedilanthus and both of them belonged to the tribe Euphorbieae; Sapium was related to Hura and they belonged to one independent group while according to Nguyen Nghia Thin: the first genus was put in the tribe Hippomaneae and the latter in the tribe Hureae.